The investigation of the effectiveness of sociopsychological training - Chomentauskas, G.; Lepeška, V. (Psichologija, 1990)
The necessity of a wider understanding of sociopsychological training is discussed in the paper. Not only a behavioral aspect, but also changes in the attitude towards people ( social decentration, social perception, etc. ) and towards their own self ( self-image enrichment, integration, etc. ) should be taken into account. The effectiveness of training should be measured in accordance with the aims discussed. The results of investigating 39 persons using the personality semantic differentia1 are presented. The factorial analysis of the data revealed changes in the semantic structure of self and other people perception which were induced by sociopsychological training. More consistent and less controversial self and other people perception was the main in structural change detected.
Keywords: sociopsychological training; effectiveness of training